2021
DOI: 10.21203/rs.3.rs-296261/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated exome and RNA sequencing of TFE3-translocation renal cell carcinoma

Abstract: TFE3-translocation renal cell carcinoma (TFE3-tRCC) is a rare and heterogeneous subtype of kidney cancer that has no standard treatment for advanced disease. We described comprehensive molecular characteristics of 63 untreated primary TFE3-tRCCs based on whole-exome and RNA sequencing. TFE3-tRCC is highly heterogeneous, both clinicopathologically and genotypically. ASPSCR1-TFE3 fusion, certain fusion isoforms and high somatic copy number alteration burdens were associated with aggressive features and poor outc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(57 citation statements)
references
References 0 publications
1
56
0
Order By: Relevance
“…Furthermore, TFE3 could promote the endolysosomal deprivation reaction by inducing the expression of autolysosomal genes [33,34]. Recently, Zeng et al demonstrated that lysosomal and autophagy pathways were significantly upregulated in TFE3-tRCC [35]. Previous studies indicated that elevated doses of crizotinib can induce autophagy in alveolar rhabdomyosarcoma cells [36] and that autophagy is required for crizotinib-induced apoptosis in MET-amplified gastric cancer cells [23].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TFE3 could promote the endolysosomal deprivation reaction by inducing the expression of autolysosomal genes [33,34]. Recently, Zeng et al demonstrated that lysosomal and autophagy pathways were significantly upregulated in TFE3-tRCC [35]. Previous studies indicated that elevated doses of crizotinib can induce autophagy in alveolar rhabdomyosarcoma cells [36] and that autophagy is required for crizotinib-induced apoptosis in MET-amplified gastric cancer cells [23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, compared with CCRCC, TFE3-tRCC also showed significantly higher levels of phospho-S6 and phospho-4EBP1 confirming upregulation of PI3K/AKT/mTOR pathway 34. Because of the complex transcriptomic and genomic landscapes, high molecular heterogeneity and low immunogenicity, TFE3-tRCC remains a therapeutic challenge and requires a combination therapeutic regimens including radiotherapy, chemotherapy, immunotherapy plus MET , TKI , and mTOR inhibitors 25,26,34…”
Section: Molecular Features Of Tfe3-translocation Renal Cell Carcinomamentioning
confidence: 99%
“…TFE3 gene maps to Xp11.23 is a Transcription Factor binding to IGHM Enhancer 3 and a member of the microphthalmia-associated transcription factor family MiTF 24. This helix-loop-helix leucine zipper transcription factor binds DNA as heterodimer forming an oncogenic fusion in RCC with over 20 different partner genes 25,26. This rearranged TFE3 oncogenic fusion plays a central role in transcriptional dysregulation forming a constitutively active promoter and thus upregulating the expression of >300 genes involved in cell growth, proliferation, and invasiveness including MET , HIF1A , cathepsin-K , CYP17A1 , UPP1 , etc 25–29.…”
Section: Molecular Features Of Tfe3-translocation Renal Cell Carcinomamentioning
confidence: 99%
See 2 more Smart Citations